2020
DOI: 10.1021/acssynbio.9b00143
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide CRISPRi-Based Identification of Targets for Decoupling Growth from Production

Abstract: Growth decoupling can be used to optimize microbial production of biobased compounds by inhibiting excess biomass formation and redirect carbon flux from growth to product formation. However, identifying suitable genetic targets through rational design is challenging. Here, we conduct a genome-wide CRISPRi screen to discover growth switches suitable for decoupling growth and production. Using an sgRNA library covering 12 238 loci in the Escherichia coli genome, we screen for targets that inhibit growth while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Knockdowns with CRSIPR interference were also used for synthetic growth switches. A CRISPRi library targeting more than 12 000 loci in the E. coli genome, identified targets that could efficiently decouple growth from production (Li et al 2020). Therefore, the authors measured which CRISPRi targets reduce growth and which targets increase production of GFP, and the overlap between these targets were promising targets for an effective growth switch.…”
Section: Non-growing Bacteria In Industrial Biotechnologymentioning
confidence: 99%
“…Knockdowns with CRSIPR interference were also used for synthetic growth switches. A CRISPRi library targeting more than 12 000 loci in the E. coli genome, identified targets that could efficiently decouple growth from production (Li et al 2020). Therefore, the authors measured which CRISPRi targets reduce growth and which targets increase production of GFP, and the overlap between these targets were promising targets for an effective growth switch.…”
Section: Non-growing Bacteria In Industrial Biotechnologymentioning
confidence: 99%
“…It is difficult to predict exactly how these polar effects might have impacted the results of this study. However, in our previous library screen, repression of eno and yciH did not result in significant inhibition of growth or an increase in GFP production, indicating that the results seen for pyrF and pyrG inhibition are not affected by downstream eno and yciH inhibition, respectively (S. Li et al, 2020).…”
Section: Resultsmentioning
confidence: 85%
“…Partial CRISPRi‐based inhibition of citrate synthase GltA increased the productivity of butanol in the cyanobacteria Synechocystis (Shabestary et al, 2018), and CRISPRi‐based inhibition of pyrF improved the yield of mevalonate almost fivefold in E. coli (S. Li, Jendresen, Grünberger et al, 2016). To screen the E. coli genome for additional promising growth decoupling targets, we established a genome‐wide sgRNA library and screened it to identify several targets that increased the green fluorescent protein (GFP) production and inhibited growth (S. Li et al, 2020). The results from this study indicated an enrichment of promising targets among genes involved in biosynthesis of purines and pyrimidines.…”
Section: Introductionmentioning
confidence: 99%
“…PCC 6803 lead to the identification of gltA and pcnB facilitating the productivity of L-lactate and bcp2, the L-lactate tolerance related gene (Yao et al, 2020). A pooled CRISPRi screen facilitated the discovery of growth switches sibB/ibsB, which can be applied to decoupling cell growth and protein production in E. coli (Li et al, 2020).…”
Section: Application Of Crispri In High-throughput Screenmentioning
confidence: 99%